Idioms of Human Mental Abilities' Negative Assessment Semantics in English and Spanish - Butko, Natalia (Studia Philologica, 2025)
This research deals with the category of evaluation and assessment in phraseology, in particular its usage in two European languages, English and Spanish, in comparison. It reveals the negative semantics phraseological units (PUs) study and negative assessment creating methods analysis in phraseological formations with a negative attitude towards the mental abilities of a man, some peculiarities in their functioning in both languages. It was found out how a negative evaluation in a phraseological unit can be created and what it depends on. The differences between its usage in English and Spanish PUs described. Qualitative and quantitative analysis of a man’s mental abilities negative assessment phraseological units is given.